Pengajaran Bahasa Inggris dan Intercultural Communication Competence: Analisis Pidato Helena Merschdorf - Desyrianti Ramadhani; Muhammad Fauzan Izzaldin Hakam; Syafiq Al Islam; Ifan Iskandar (Syntax Corporation Indonesia, 2023)
Intercultural Communication Competence (ICC) is becoming more important nowadays because of the modern social issues in society. Previous studies tried to insert ICC into English Language Teaching (ELT) in order to help solving these issues. However, little attention has been paid to the dimension and components of ICC. Library research method was conducted with the script of the speech from Helena Merschdorf regarding intercultural communication as the primary source and several other books and articles as secondary resources. There are two primary aims of this study: 1. To analyse the components and dimensions of ICC based on Helena Merschdorf’s speech. 2. To know the components and dimensions of ICC based on Helena Merschdorf’s speech that can be inserted in ELT. The result indicate that the speech include all components and dimesions of ICC and each component and dimension of ICC can be inserted into ELT.